Real world clinical outcomes from targeted intraoperative radiotherapy (TARGIT-IORT) during lumpectomy for breast cancer: data from a large cohort at a national cancer institute - Vinante, Lorenzo; Vaidya, Jayant Sharad; Caroli, Angela; Mileto, Mario; Piccoli, Erica; Avanzo, Michele; Barresi, Loredana; Marson, Marta; Montico, Marcella; Baboci, Lorena; Perin, Tiziana; Urbani, Martina; et al. (Frontiers in Oncology, 2024)
IntroductionRandomised evidence supports the use of partial breast irradiation (PBI) with targeted intraoperative radiotherapy (TARGIT-IORT) for early stage breast cancer, but prospective data from real-world adoption of this technique is also important. The aim of this study was to determine if the outcome reported in TARGIT-A trial could be replicated in large cohort of early stage breast cancer treated with TARGIT-IORT.MethodsThis prospective observational study analysed all patients treated with TARGIT-IORT between 2004 and 2021 in a single national cancer institute. TARGIT-IORT during lumpectomy was performed according to the risk-adapted TARGIT-A protocol using the Intrabeam® device. We analysed the completeness of follow up, 5-year in-breast-tumour-recurrence (IBTR), long term local recurrence free survival, distant disease-free survival, overall survival and breast-cancer-related survival, using the Kaplan-Meier method. A covariate analysis was performed to investigate risk factors for IBTR. We also analysed high grade toxicity events.ResultsThe study included 814 patients and the a median follow up was 72 months. The majority of patients (60.3%) received TARGIT-IORT as PBI modality (“exclusive IORT” group); 39.7% received additional EBRT. There was no significant difference between the 5 years IBTR for the whole study population and the “exclusive IORT” cohort (1.6% (95%CI=1.1-2.1%) and 2.5% (95%CI=1.7%-3.3%) respectively). 5 years overall survival and tumour related survival were >95%. In 21% of patients with recurrence, breast was preserved. Radiotherapy toxicity (CTCAE Grade>2) was very rare (0.9%).ConclusionsThis large single institute study found that breast cancer control and survival outcomes with TARGIT-IORT were consistent with TARGIT-A trial results. This “real world” experience confirmed that the randomised evidence showing the value of TARGIT-IORT as partial breast irradiation modality that can be replicated in routine clinical practice.